A fuzzy DEMATEL-based approach for evaluation of risks in green initiatives in supply chain. Issue 2 (2016) - Mangla, Sachin K.; Kumar, Pradeep; Barua, Mukesh Kumar
The implementation of green/green supply chain (GSC) initiatives is relatively difficult for the point of view of industries due to involvement of different risks. Decision evaluation and assessment of these risks can help industries to formulate strategies and suggest appropriate measures for managing the GSC effectively. For this motive, this paper recognises the eight evaluation GSC risks with two main dimensions based on relevant literature and ten industrial experts' inputs at an Indian plastic manufacturer. The current research proposes to use a fuzzy decision making trial and evaluation laboratory (DEMATEL) methodology for analysing the causal relations among the risks. The used fuzzy DEMATEL approach is useful in dealing with human bias and ambiguity involved in studying the interrelationship between the evaluated risks. Research findings indicate that operational risks and supply risks have the top significant influences in adopting and implementing effective GSC initiatives in business. Implications for managers and conclusions are discussed in the end.